2018
DOI: 10.3892/or.2018.6649
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‑572 functions as an oncogene and a potential biomarker for renal cell carcinoma prognosis

Abstract: Renal cell carcinoma (RCC) is the third most common urological malignancy in the USA and represents 2‑3% of all adult malignancies. Furthermore, the incidence of RCC has been progressively increasing over recent years. Although the morbidity of treatment has decreased with the use of multidisciplinary synthetic therapy, the prognosis of terminal cancer remains poor, with a 5‑year survival rate of 5‑10%. MicroRNAs (miRs) have been correlated with the regulation of 30‑60% of the protein-coding genes and act as o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…And miR-106b levels were not correlated with sex, age, whilst noticeable difference was found between miR-106 expression and tumor stage, pathology grade and lymph node metastasis. These outcomes suggested that miR-106b may serve as a potential independent prognostic marker for RCC, which functioned similarly to miR-21 and miR-223, 43 miR-154-5p, 44 miR-572 45 and so on.…”
Section: Discussionmentioning
confidence: 96%
“…And miR-106b levels were not correlated with sex, age, whilst noticeable difference was found between miR-106 expression and tumor stage, pathology grade and lymph node metastasis. These outcomes suggested that miR-106b may serve as a potential independent prognostic marker for RCC, which functioned similarly to miR-21 and miR-223, 43 miR-154-5p, 44 miR-572 45 and so on.…”
Section: Discussionmentioning
confidence: 96%
“…As for miR-193a-3p, it was shown to target the tumor suppressor phosphatase and tensin homolog (PTEN) and mediate the PI3K/Akt pathway, thereby promoting RCC cell growth and progression ( Liu L. et al, 2017 ; Pan Y. et al, 2018 ). miR-572 likewise represents an oncomir in RCC pathogenesis by enhancing proliferation and invasion and inhibiting tumor cell apoptosis by suppressing NF2/Hippo signaling ( Guan et al, 2018 ; Pan et al, 2018a ). On the other hand, miR-28-5p ( Wang et al, 2016 ) and miR-362 ( Zou et al, 2016 ; Zhu et al, 2020 ) were suggested as tumor-suppressive miRNAs in RCC, although the miR-362 serum levels were increased in the study by Wang et al (2015) .…”
Section: Circulating Mirnas In Rccmentioning
confidence: 99%
“…Interestingly, we also observed the significant downregulation of several miRNAs. Among them, some are already described in literature such as miRNA-572, prognosis biomarker for renal cell carcinoma and sclerosis [44,45], or miRNA-769, included in a miRNA panel for discrimination between Mycobacterium tuberculosis infected and healthy individuals [46].…”
Section: Discussionmentioning
confidence: 99%